Influence of Organizational Culture and Leadership Style on Job Satisfaction on Tax Service Office Employees: Mediated Role of Work-Life Balance Policy - Hastuti, Ganiahariani; Meutia,, Meutia,; Sultan, Zulkifli (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – The purpose of this study is to obtain empirical evidence of the ability of organizational culture and leadership style in encouraging increased job satisfaction, both directly and through the mediation of work-life balance policy. Methodology/approach – This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires distributed to 111 Tax Service Office employees in Malang City (North Malang Tax Office and South Malang Tax Office). The sample was determined following the Slovin formula. Findings – Empirical evidence shows that both organizational culture and leadership style are able to encourage increased job satisfaction, both directly and through the mediation of work-life balance policy, which can act as strong mediation. Novelty/value – The results obtained show that the work-life balance policy does have meaning for government institutions such as the Tax Service Office in Malang City. How could it not, the work-life balance policy is able to mediate the influence of organizational culture and leadership style on job satisfaction.